Diagnosis of Neurocysticercosis by Detection of Taenia solium DNA Using a Global DNA Screening Platform - Harrington, Amanda T. (2009)
Neurocysticercosis is caused by Taenia solium infection of the brain. Diagnosis is most often made by visualization of the parasitic scolex by magnetic resonance imaging of the brain or by characteristic neuroimaging findings with serologic test results positive for T. solium. A patient who presents with a solitary brain lesion usually poses a diagnostic dilemma, because the differential diagnosis often includes neurocysticercosis and other infections or neoplasm. Although the sensitivity of serologic testing for T. solium approaches 100% in patients with multiple intraparenchymal cysts, the sensitivity of testing for patients with solitary cysts is <50%, which makes serologic testing a less useful diagnostic tool for patients with solitary central nervous system (CNS) lesions. We describe 2 patients with solitary CNS lesions who received a neurocysticercosis diagnosis after identification of T. solium DNA in brain biopsy tissue with use of a global DNA screening platform. Global screening is a promising tool for the diagnosis of CNS infection, especially when traditional diagnostic tools are insensitive.